Activation of mammalian target of rapamycin pathway confers adverse outcome in nonsmall cell lung carcinoma - Liu, Dan; Huang, Yi; Chen, Bojiang; Zeng, Jing; Guo, Na; Zhang, Shangfu; Liu, Lunxu; Xu, Hong; Mo, Xianming; Li, Weimin (Cancer, 2011)
BACKGROUND: Dysregulation of the mammalian target of rapamycin (mTOR) pathway has been shown to contribute to tumorigenesis. This study explored protein expression profiles of mTOR pathway and the relationship with prognosis in patients with nonsmall cell lung carcinoma (NSCLC). METHODS: The protein expression profiles of mTOR/phosphorylated (p‐)mTOR, phosphoinositide‐dependent kinase 1 (PDK1)/p‐PDK1, p‐Akt1, and P70 ribosomal protein S6 kinase (P70S6K)/p‐P70S6K were determined via immunohistochemical staining assay. The clinical prognostic values of both single and combined protein expression were investigated with univariate and multivariate survival analysis. RESULTS: Compared with normal lung tissues, the protein levels of mTOR/p‐mTOR, p‐Akt1 Ser473/Thr308, and P70S6K/p‐P70S6K were higher (all P < .05), whereas p‐PDK1 was lower (P < .05) in tumor tissues. p‐mTOR expression was associated with histological differentiation, histological type, lymph node invasion, and stage (all P < .05). Overall survival in NSCLC patients was significantly shorter in cases with positive phenotype for p‐mTOR, p‐PDK1, and p‐P70S6K (all P < .05). Subjects with coexpression of any 2 of p‐mTOR, p‐PDK1, p‐Akt1 Ser473, and p‐P70S6K demonstrated worse prognosis than those expressing no biomarker or any 1 biomarker alone (all P < .05). Multivariate analysis showed that the combination of p‐mTOR/p‐P70S6K is an independent prognostic factor in addition to tumor stage. CONCLUSIONS: This study provides clinical evidence that activated components of mTOR pathway, not total protein, are predictors of poor prognosis in NSCLC. Moreover, evaluating protein‐expression profiles of these molecules might be a new strategy for individual therapy in subjects with NSCLC. Cancer 2011;. © 2011 American Cancer Society. This study provided the first clinical evidence that activated components of mammalian target of rapamycin pathway, not total protein, are predictors of poor prognosis in nonsmall cell lung carcinoma (NSCLC). Moreover, evaluating protein‐expression profiles of these molecules might be a new strategy for individual therapy in subjects with NSCLC.